Aqueous Biphasic Systems for the Synthesis of Formates by Catalytic CO2 Hydrogenation: Integrated Reaction and Catalyst Separation for CO2‐Scrubbing Solutions. Issue 6 (17th February 2017) - Scott, Martin; Blas Molinos, Beatriz; Westhues, Christian; Franciò, Giancarlo; Leitner, Walter
Abstract: Aqueous biphasic systems were investigated for the production of formate–amine adducts by metal‐catalyzed CO2 hydrogenation, including typical scrubbing solutions as feedstocks. Different hydrophobic organic solvents and ionic liquids could be employed as the stationary phase for cis ‐[Ru(dppm)2 Cl2 ] (dppm=bis‐diphenylphosphinomethane) as prototypical catalyst without any modification or tagging of the complex. The amines were found to partition between the two phases depending on their structure, whereas the formate–amine adducts were nearly quantitatively extracted into the aqueous phase, providing a favorable phase behavior for the envisaged integrated reaction/separation sequence. The solvent pair of methyl isobutyl carbinol (MIBC) and water led to the most practical and productive system and repeated use of the catalyst phase was demonstrated. The highest single batch activity with a TOFav of approximately 35 000 h −1 and an initial TOF of approximately 180 000 h −1 was achieved in the presence of NEt3 . Owing to higher stability, the highest productivities were obtained with methyl diethanolamine (Aminosol CST 115) and monoethanolamine (MEA), which are used in commercial scale CO2 ‐scrubbing processes. Saturated aqueous solutions (CO2 overpressure 5–10 bar) of MEA could be converted into the corresponding formate adducts with average turnover frequencies up to 14×10 3  h −1 with an overall yield of 70 % based on the amine, corresponding to a total turnover number of 150 000 over eleven recycling experiments. This opens the possibility for integrated approaches to carbon capture and utilization. Abstract : Scrubs up well : An integrated process for the synthesis of formate–amine adducts based on aqueous biphasic catalysis is presented. The solvent pair methyl isobutyl carbinol (MIBC)/water led to the most productive system with a ruthenium complex as catalyst. Re‐use of the catalyst phase was demonstrated. This approach enables the direct hydrogenation of carbon dioxide in aqueous solutions of monoethanolamine and methyl diethanolamine, as used in carbon capture technologies, with a total turnover number of up to 150 000.